Economic loss attributable to premature deaths and morbidity among adolescents in India and its states - G Anil Kumar; Anamika Pandey; Rakhi Dandona (BMC Medicine)
Abstract Background India’s large youth population presents a significant opportunity to harness the demographic dividend. The disease burden in adolescents could be a hindrance for the future economy if not appropriately addressed. Methods We utilised the data on the number of adolescent deaths and attributable years lived with disability (morbidity) in every state of India as part of the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2021. We estimated the economic impact as the cost of lost output due to premature adolescent deaths and morbidity for every state of India in 2021, using an output-based method. The cost of lost output is reported in US Dollars (USD) and as a percentage of Gross Domestic Product (GDP) for all diseases/conditions together, and separately for communicable diseases (CDs), non-communicable diseases (NCDs), and injuries. Results The lost output from premature deaths and morbidity attributable to adolescents was USD 9.87 (95% CI 9.04–10.71) and USD 28.13 (95% CI 20.53–37.71) billion respectively, in India in 2021. The total economic loss of USD 38.01 billion (95% CI 29.57–48.41) was 1.30% (1.01–1.65) of India’s GDP. The total economic loss as a percentage of the state’s GDP varied 3.42 times between the states in 2021, ranging from 2.43% in Bihar to 0.71% in Sikkim. The total economic loss due to CDs, NCDs, and injuries was estimated at 0.45%, 0.69% and 0.16% of India’s GDP in 2021, with significant variations across the states. Conclusions Strengthening the Indian Adolescent Health Strategy to address the diseases/ conditions contributing most to the total economic loss is needed to facilitate substantial avoidance of the high economic losses attributable to adolescent premature deaths and morbidity in India.